Classification and Recognition of Fluvial Geomorphic Units Based on Process and Form Relationship - YU Zicheng; DENG Rui; ZHANG Jing; ZHAO Jinyong; DING Yang; LI Xuan (Renmin Zhujiang)
Clarifying the types of fluvial geomorphic units and their spatial distribution can better recognize and understand rivers.In the face of problems such as the imperfection and difficult implementation of the existing classification and recognition methods of geomorphic units in China,the mature classification systems of Fryirs and Brierley geomorphic units in other countries were summarized,and the process and form relationship of different geomorphic unit types was sorted out.The Daning River,a first-level tributary of the Yangtze River,was taken as a practical case.The classification and recognition process of fluvial geomorphic units based on the process and form relationship was formed,and the spatial distribution of geomorphic units was defined by combining with the field survey data of air,sky,and ground.The classification system of Fryirs and Brierley geomorphic units was divided into four categories:alluvial and erosional bedrock and boulder units,mid-channel sedimentary units,riparian sedimentary units,and alluvial and erosional fine-grained units,including 42 types of terrace falls,deep pools,and point beaches.The types of geomorphic units included in the confluence section of the Lianghekou area of the Daning River and Houxi River were tandem plunge,rapid beach,slippery water,deep pool,shallow beach,slow flow area,side beach,and heart beach,accounting for 16.43%,21.51%,7.21%,20.45%,16.90%,13.59%,and 3.91% of the studied river section,respectively.Quantitative analysis of the spatial distribution of geomorphic units can provide theoretical support for the restoration of damaged habitats and habitat assessment in the river section.